Improved energy performance of small-scale pneumatic dryers used for processing cassava in Africa - Precoppe, M.; Tran, T.; Chapuis, Arnaud; Müller, Joachim; Abass, A. (Elsevier, 2016)
Cassava (Manihot esculenta) is the most important staple food in sub-Saharan Africa. However, the shelf-life of the crop is short and, for this reason, the roots are usually processed into more stable products like cassava flour by village-based enterprises. Most of these enterprises use small-scale locally built pneumatic dryers, but such dryers still need further development, so the objective of this research was to improve their energy performance. Experiments were conducted at two cassava processing centres, one in Tanzania and one in Nigeria. Sensors were installed on the dryers, product samples were collected and the mass and energy balance of the equipment analysed, allowing the dryers' minimum air mass flow rates to be calculated. The air mass flow rates of both dryers were then reduced to a level approximating the minimum value. In Tanzania, the air mass flow rate of the dryer was reduced by 24%, while in Nigeria it was reduced by 14%. In both locations, the modifications decreased the dryers' heat input without jeopardising evaporation rates, and so not affecting the final moisture content of the dry products. Air temperatures at the dryer outlets decreased and relative humidity increased, while enthalpy remained unchanged. The energy required to evaporate 1 kg of water decreased by 20% in Tanzania and by 13% in Nigeria. The modification also improved energy efficiency by 25% in Tanzania and by 14% in Nigeria. However, in Nigeria, where yellow cassava flour was being used, the dryer modifications resulted in greater product colour losses.